EFFECT OF âKOMBA-KOMBAâ PRUNING COMPOST AND PLANTING TIME OF MUNGBEAN IN INTERCROPPING WITH MAIZE ON YIELD AND SOIL FAUNA - Sabaruddin, Laode; Kilowasid, Laode Muhammad Harjoni; Syaf, Hasbullah (AGRIVITA, Journal of Agricultural Science, 2013)
Soil fauna plays an important role in decomposition and nutrient mineralization. The objective of this research was to study the effect of "komba-komba" compost and planting time of mungbean intercropped with maize on yield and soil fauna. The research was conducted in research station of Agricultural Faculty, Haluoleo University. The experiment was laid out using split plot design with two factors ("komba-komba" compost and planting time of mungbean intercropped with maize). The result indicated that the highest net assimilation rate (NAR) of mungbean 5.78 g per cm2 per week was obtained in the komba-komba compost 10 ton per haÂ  with planting time of mungbean at 14 days after planting (DAP) maize whereas NAR of maize 5.50 g per cm2 per week was obtained in the planting time of mungbean at 14Â  DAP maize. Coleoptera and Hymenoptera (Formicidae) were dominant and Shannons diversity index ranged between 0.32 and 1.28. LER values tended to increase with the addition of "komba-komba" compost in soil and time variation of planting mungbean intercropped with maize. The relation between Shannons diversity and LER values was variable. Keywords: soil fauna, compost, intercro-pping, planting time, assimilation, LER